Handbook of Ecomaterials - Martínez, Leticia Myriam Torres; Kharissova, Oxana Vasilievna; Kharisov, Boris Ildusovich; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
In this handbook, the editors systematically present the maximum possible number of known eco-materials, including "cyclic" materials; materials for ecology and environmental protection; materials for society and human health; and materials for energy based on two main criteria: their sources and their functions. Eco-materials (also called "environmentally friendly materials" or "environmentally preferable" materials) are materials that enhance, or refrain from damaging, the environment throughout their life cycles. The chapters are written by global leaders in their fields. The book will cater to the strong and ever-increasing demand for energy, benign materials, and cost efficiency. Eco-materials is arguably one of the most important fields of modern science & technology. .
Keywords: Materials; Renewable energy sources; Biomaterials; Sustainability; Materials Engineering; Renewable Energy; Biomaterials; Sustainability